The Uncertain Doctrine of Part Performance - Frankel, Susy (Victoria University of Wellington Law Review, 2011)
This article is about the doctrine of part performance and its application in New Zealand's law of contract. In order to be enforceable contracts for the disposition of land must be in writing and must be signed by the person against whom the contract is enforced. Where these requirements have not been met the courts have evolved the doctrine of part performance to enable a contract to be enforceable where that is equitable. This article outlines the doctrine of part performance as found in New Zealand and argues that it is so uncertain that its existence does not benefit litigants or would be litigants. The article concludes that the difficulties with the doctrine of part performance mean that it is not a clear and effective mechanism again the misuse of the writing requirement and, therefore, adds to other reasons to repeal the writing requirement for contracts for the sale of land.